Computational Ways to Enhance Protein Inhibitor Design - Jernigan, Robert L.; Sankar, Kannan; Jia, Kejue; Faraggi, Eshel; Kloczkowski, Andrzej (Frontiers in Molecular Biosciences, 2021)
Two new computational approaches are described to aid the design of new peptide-based drugs by evaluating ensembles of protein structures from their dynamics, and the assessment of the structures using empirical contact potential. This builds on the concept that conformational variability can aid the binding process and, for disordered proteins, can even facilitate the binding of more diverse ligands. This latter consideration should mean that such a design process should be less restrictive so that multiple designed inhibitors might be effective. The example chosen here focuses on proteins/peptides binding to hemagglutinin (HA) to block the large-scale conformational change occurring during its activation. Variability in the conformations are considered from sets of experimental structures, or as an alternative their simple computed dynamics, and the set of designed peptides/small proteins from Baker (1) designed to bind to hemagglutinin, is the large set considered are assessed with the new empirical contact potentials.